2008
DOI: 10.1002/bit.22153
|View full text |Cite
|
Sign up to set email alerts
|

Design of well and groove microchannel bioreactors for cell culture

Abstract: Microfluidic bioreactors have been shown valuable for various cellular applications. The use of micro-wells/grooves bioreactors, in which micro-topographical features are used to protect sensitive cells from the detrimental effects of fluidic shear stress, is a promising approach to culture sensitive cells in these perfusion microsystems. However, such devices exhibit substantially different fluid dynamics and mass transport characteristics compared to conventional planar microchannel reactors. In order to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 25 publications
2
32
0
Order By: Relevance
“…Many reactions have been tested in microchannel reactors such as water gas shift [22], steam reforming [25], partial oxidation [26][27][28], Fischer Tropsch synthesis [29,30], synthesis of methanol [31], methane oxidative coupling [32], photocatalysis [33], catalytic combustion [34] and as a bioreactor [35]. These are just a few examples and the applications are spreading quickly.…”
Section: Microchannel Reactorsmentioning
confidence: 99%
“…Many reactions have been tested in microchannel reactors such as water gas shift [22], steam reforming [25], partial oxidation [26][27][28], Fischer Tropsch synthesis [29,30], synthesis of methanol [31], methane oxidative coupling [32], photocatalysis [33], catalytic combustion [34] and as a bioreactor [35]. These are just a few examples and the applications are spreading quickly.…”
Section: Microchannel Reactorsmentioning
confidence: 99%
“…Tilles et al demonstrated that with internal membrane oxygenation in the bioreactor, flow conditions that resulted in low wall shear stresses generated higher albumin and urea synthetic rates compared with flow conditions that resulted in high wall shear stresses. Detailed parametric study of well and groove microchannel bioreactors was presented by Korin et al 28 Operation conditions and design parameters were theoretically examined via a numerical model. The complex flow pattern obtained at grooves of various depths was studied, and the shear protection factor compared with planar microchannels was evaluated.…”
Section: Dynamic (Perfusion) Cell Culturementioning
confidence: 99%
“…The oxygen consumption rate (OCR) for the EB bulk was set according to Michaelis-Mentin kinetics with respect to oxygen concentration (Cochran et al 2006;Korin et al 2009):…”
Section: Numerical Simulationsmentioning
confidence: 99%